Void dynamics - Padilla, Nelson David (2014)
Cosmic voids are becoming key players in testing the physics of our Universe. Here we concentrate on the abundances and the dynamics of voids as these are among the best candidates to provide information on cosmological parameters. Cai, Padilla & Li (2014) use the abundance of voids to tell apart Hu & Sawicki f(R) models from General Relativity. An interesting result is that even though, as expected, voids in the dark matter field are emptier in f(R) gravity due to the fifth force expelling away from the void centres, this result is reversed when haloes are used to find voids. The abundance of voids in this case becomes even lower in f(R) compared to GR for large voids. Still, the differences are significant and this provides a way to tell apart these models. The velocity field differences between f(R) and GR, on the other hand, are the same for halo voids and for dark matter voids. Paz et al. (2013), concentrate on the velocity profiles around voids. First they show the necessity of four parameters to describe the density profiles around voids given two distinct void populations, voids-in-voids and voids-in-clouds. This profile is used to predict peculiar velocities around voids, and the combination of the latter with void density profiles allows the construction of model void-galaxy cross-correlation functions with redshift space distortions. When these models are tuned to fit the measured correlation functions for voids and galaxies in the Sloan Digital Sky Survey, small voids are found to be of the void-in-cloud type, whereas larger ones are consistent with being void-in-void. This is a novel result that is obtained directly from redshift space data around voids. These profiles can be used to remove systematics on void-galaxy Alcock-Pacinsky tests coming from redshift-space distortions.